Análise de citações da produção científica de uma comunidade: a construção de uma ferramenta e sua aplicação em um acervo de teses e dissertações do PPGCI-UFMG - Igor Campos Leal (2005)
Due to the current technological evolution, internet facilities and such wide range of media communication, an information explosion (or information bug) has been growing up lately, which is not a newness, specially in scientific area. Researchers have never had so much facility accessing the published scientific material. However, analysis mechanisms of the mentioned material are still not that accessible. Based on these points this work will present the development of a citation analysis tool, area of study of the discipline Information Processing, better known as bibliometrics. It was divided in two phases: the first one refers to the tool implementation and the second one to the experimental part. It has been worked on the universe of 55 thesis and dissertations approved by the UFMG Information Science Post-Graduate Program, with the purpose to verify the usability of the developed tool. Trough these documents was created a digital library, using as its base the framework of digital library creation named Dspace, which was developed by MIT and HP. A new module was added to Dspace, the citation analysis, trough wich all the 4.495 bibliographic references present in the 55 documents were analyzed according to the following indicators: published year, publication type, origin country, author of the cited work, title and language used. Such indicators could be analyzed subdividing by subarea of research, advisor, general and for a single document. The charts generated by the developed tool have demonstrated the power of the bibliometrics analysis. The dissertation concludes that techniques like this are important and necessary to the survey of the bases for analyze the scientific communication and studies about the epistemology of specific knowledge areas in Brazil. This tool would be potentialized if it used by others scientific communities, in order to give them a unique place of analysis of what they have produced in the stricto sensu postgraduate levels in Brazil.